Diapause in Stingless Bees (Hymenoptera: Apidae) - Charles Fernando dos Santos (2022)
Submitted by Biblioteca Suporte PUCRS (biblioteca.suporte@pucrs.br) on 2022-09-21T13:25:04Z No. of bitstreams: 2 Diapause_in_Stingless_Bees_Hymenoptera_Apidae.pdf: 1204390 bytes, checksum: b640dba2decad7090475d1e4bddc1407 (MD5) Diapause_in_Stingless_Bees_Hymenoptera_Apidae.pdf: 1204390 bytes, checksum: b640dba2decad7090475d1e4bddc1407 (MD5)